Auditoría tributaria y su incidencia en el cumplimiento de las obligaciones fiscales en el centro comercial “Su Economía” del cantón Valencia, provincia de Los Ríos, periodo 2022. - García Álava, Arianna Mickaela (2023)
The present work addressed the "Tax Audit and its impact on compliance with tax obligations in the "Su Economía" Shopping Center in the canton of Valencia, Los Ríos province, period 2022". The main objective was to apply a tax audit to verify compliance with tax obligations, ensuring proper compliance with legal and tax provisions in the entity. Alternatively, the methodology used in the study was based on different types of research, such as bibliographic and descriptive. In addition, field research was carried out where interviews and surveys were conducted with the employees of the entity to obtain additional information and enrich the research work. The results of the applied audit revealed that the entity effectively complies with its tax obligations, guaranteeing the integrity and transparency of its business activities. The audit also identified areas for improvement to ensure compliance with established regulations. In addition, the level of confidence obtained in the audit was 82%, which indicates a high degree of certainty in the entity's tax situation. However, a control risk of 18% was identified, indicating that there are areas that could be improved to strengthen effective compliance with tax obligations. Finally, based on the data collected and analyzed, a manual of tax procedures and policies was designed that contributed to effective compliance with tax obligations, strengthening the management of the "Su Economía" Shopping Center.